2013
DOI: 10.1371/journal.pone.0065549
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Induction of Growth Differentiation Factor 15 Attenuates Endothelial Cell Apoptosis in Response to High Glucose Stimulus

Abstract: Growth differentiation factor 15 (GDF15), a direct target gene of p53, is a multifunctional member of the TGF-β/BMP superfamily. GDF15 can be induced and is implicated as a key secretory cytokine in response to multiple cellular stimuli. Accumulating evidence indicates that GDF15 is associated with the development and prognosis of diabetes mellitus, while whether GDF15 can be induced by high glucose is unknown. In the present study, we revealed that high glucose could induce GDF15 expression and secretion in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 51 publications
(90 reference statements)
3
78
1
Order By: Relevance
“…GDF15 plays important roles in multiple pathologies including cardiovascular diseases, cancer, and inflammation. It has been shown that GDF15 is up-regulated by tumor suppressor p53 in response to high glucose or treatment with anti-cancer compounds (Baek et al, 2002;Li et al, 2013;Yang et al, 2003). The p53 protein is a transcription factor that responds to a variety of stresses such as DNA damage, oxidative stress, hypoxia, and metabolic stress, and it activates the expression of genes to induce cell cycle arrest, DNA repair, senescence, and cell death (Sermeus and Michiels, 2011;Sperka et al, 2012;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…GDF15 plays important roles in multiple pathologies including cardiovascular diseases, cancer, and inflammation. It has been shown that GDF15 is up-regulated by tumor suppressor p53 in response to high glucose or treatment with anti-cancer compounds (Baek et al, 2002;Li et al, 2013;Yang et al, 2003). The p53 protein is a transcription factor that responds to a variety of stresses such as DNA damage, oxidative stress, hypoxia, and metabolic stress, and it activates the expression of genes to induce cell cycle arrest, DNA repair, senescence, and cell death (Sermeus and Michiels, 2011;Sperka et al, 2012;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It prevented low potassium induced death in cerebellar granule cells (Subramaniam et al, 2003) and had an anti-apoptotic effect on cultured cardiomyocytes, subjected to simulated ischemia/reperfusion and endothelial cells subjected to hypoxia (Kempf et al, 2006; Song et al, 2012) or high glucose stimulus (Li et al, 2013a). Agarwal et al showed that application of exogenous GDF-15 or its constitutive expression from a cDNA provided remarkable protection of p53-null cells from apoptosis mediated by phosphonacetyl-l-aspartate, which blocks the synthesis of pyrimidines (Agarwal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These results reinforce that GDF15 is an antihypertrophic factor. Other studies indicate that GDF‐15 is cardioprotective by activating the phosphoinositide 3‐kinase/AKT/endothelial nitric oxide synthase/NO pathway . In general, TGF‐β signaling activation was previously viewed as detrimental to cardiac function, resulting in cardiac remodeling, including hypertrophy and fibrosis.…”
Section: Gdf‐8 and Gdf‐15mentioning
confidence: 99%